Electrolyte and energy storage device

By using the combined action of the first and second additives of fluorophenyl radicals and fluoropyridine-based structures in the electrolyte of the energy storage device, the pressure increase and performance decline caused by the electrolyte decomposition and evaporation of the electrolyte under high temperature conditions is solved, and higher negative electrode stability and energy storage performance are achieved.

CN119627223APending Publication Date: 2025-03-14XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411848177.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Large energy storage devices have high heat production and poor heat dissipation in high temperature conditions, resulting in electrolyte decomposition and evaporation, and the internal pressure increases, which may even cause ignition and explosion, affecting the stability and performance of the energy storage device.

Method used

An electrolyte is adopted, which consists of a first additive and a second additive. The first additive has a fluorophenyl radical structure and the second additive has a fluoropyridine structure. The two work together to reduce the LUMO energy level of the molecular cluster, improve the stability of the negative electrode, reduce the loss of active lithium, and enhance the capacity retention rate and performance of the energy storage device at high temperatures.

Benefits of technology

Under high temperature conditions, the decomposition products formed by the combined action of the electrolyte are more stable, which can stabilize the negative electrode interface during the circulation of the energy storage device, reduce the loss of active lithium, and improve the high-temperature circulation and high-temperature storage performance of the energy storage device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627223A_ABST
    Figure CN119627223A_ABST
Patent Text Reader

Abstract

The invention provides an electrolyte and an energy storage device, the electrolyte comprises a first additive and a second additive, the first additive has a structural formula as shown in formula (I): # imgabs0 #, R1-R5 are independently selected from one or more of fluorine, hydrogen and fluoroalkyl, and R1-R5 are not hydrogen at the same time; the second additive has a structural formula as shown in a formula (II): # imgabs 1 #, R6 to R10 are respectively and independently selected from one or more of fluorine, hydrogen and fluoroalkyl, and R6 to R10 are not hydrogen at the same time. The energy storage device assembled by using the electrolyte provided by the invention has relatively good performance under a high-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of energy storage devices, and in particular to an electrolyte and an energy storage device. Background Art

[0002] With the development of the energy storage industry and the continuous advancement of energy storage device technology, energy storage devices are widely used in fields such as electric vehicles, mobile devices, and energy storage systems. However, as the energy density of large energy storage devices becomes higher and higher, the integration of battery cells in energy storage devices is also increasing. In energy storage devices such as lithium-ion batteries, in order to increase the energy density of lithium-ion batteries, the capacity of single batteries is getting larger and larger. In large-capacity batteries, the heat generation is high and the heat dissipation is poor. During operation, heat accumulates and the electrolyte is easily decomposed and evaporated, resulting in increased pressure inside the energy storage device, and may even cause the energy storage device to catch fire or explode, making the stability of the energy storage device under high temperature conditions increasingly prominent, which in turn affects the performance of the energy storage device in high temperature environments. Summary of the invention

[0003] The purpose of the embodiments of the present application is to provide an electrolyte and an energy storage device. The energy storage device assembled using the electrolyte has good performance under high temperature conditions.

[0004] The present application provides an electrolyte, the electrolyte comprising a first additive and a second additive, the first additive having a structural formula as shown in formula (I):

[0005] wherein R1 to R5 are each independently selected from one or more of fluorine, hydrogen, and fluoroalkyl, and R1 to R5 are not hydrogen at the same time;

[0006] The second additive has a structural formula as shown in formula (II): Wherein, R6 to R10 are each independently selected from one or more of fluorine, hydrogen, and fluoroalkyl, and R6 to R10 are not hydrogen at the same time.

[0007] In the electrolyte provided in the embodiment of the present application, the first additive and the second additive are used in combination, wherein the fluorophenyl free radicals generated by the reaction of the first additive have strong electrophilicity, and thus are more likely to attack the second additive. During the reduction process, the first additive transfers charge to the second additive, thereby lowering the LUMO (Lowest Unoccupied Molecular Orbital) energy level of the molecular cluster, thereby causing the first additive and the second additive to undergo a reduction reaction simultaneously. At the same time, compared with structure ① formed by adding the first additive alone to the electrolyte or structure ② formed by adding the second additive alone, in structure ③ formed by adding the first additive and the second additive at the same time in the embodiment of the present application, the pyridyl N atom contains a lone pair of electrons, which has a stronger binding effect on lithium ions, making structure ③ more difficult to be reduced. At the same time, the phenyl group in structure ③ has a large conjugated system, making structure ③ more difficult to be oxidized, thereby making structure ③ more stable relative to structure ① and structure ②, thereby making the negative electrode stability of the decomposition product formed by the combined action of the first additive and the second additive higher, so that the negative electrode interface can be stabilized during the cycle of the assembled energy storage device, while reducing the loss of active lithium, which is beneficial to improving the capacity retention rate of the energy storage device under high temperature conditions, and thus beneficial to improving the performance of the energy storage device under high temperature conditions.

[0008] In one possible embodiment, the fluoroalkyl group selected from R1 to R5 is a C1 to C3 fluoroalkyl group. Exemplarily, the C1 to C3 fluoroalkyl group selected from R1 to R5 may be a fluoromethyl group, a fluoroethyl group, a fluoropropyl group, a difluoromethyl group, a difluoroethyl group, a difluoropropyl group, a trifluoromethyl group, a trifluoroethyl group, a trifluoropropyl group, etc. In one possible embodiment, the fluoroalkyl group selected from R6 to R10 is a C1 to C3 fluoroalkyl group. Exemplarily, the C1 to C3 fluoroalkyl group selected from R6 to R10 may be a fluoromethyl group, a fluoroethyl group, a fluoropropyl group, a difluoromethyl group, a difluoroethyl group, a difluoropropyl group, a trifluoromethyl group, a trifluoroethyl group, a trifluoropropyl group, etc.

[0009] In one possible embodiment, R1 to R5 are each independently selected from one or more of fluorine, hydrogen, fluoromethyl, difluoromethyl and trifluoromethyl, and R6 to R10 are each independently selected from one or more of fluorine, hydrogen and trifluoromethyl.

[0010] In one possible embodiment, the first additive is selected from one or more of structural formula (I-1) to structural formula (I-3):

[0011]

[0012] In one possible embodiment, the second additive is selected from one or more of structural formula (II-1) to structural formula (II-3):

[0013]

[0014] In one possible implementation, based on the mass of the electrolyte, the mass fraction of the first additive is a, the mass fraction of the second additive is b, 0.02wt%≤a+b≤10wt%, which can ensure that the assembled energy storage device has good room temperature cycle performance, high temperature cycle performance and high temperature storage performance.

[0015] In a possible implementation, 0.1≤a / b≤5, which can ensure that the assembled energy storage device has good room temperature cycle performance, high temperature cycle performance and high temperature storage performance.

[0016] In a possible embodiment, the electrolyte further includes an auxiliary additive, which is one or more of cyclic sulfates and cyclic carbonates. The molecules of auxiliary additives such as cyclic sulfates or cyclic carbonates have a strong binding effect with lithium ions, and can be reduced at the interface of the negative electrode during formation, and their reduction products (such as the reduction products of cyclic sulfates are mainly organic lithium sulfates and lithium sulfonates, and the reduction products of cyclic carbonates such as fluorovinylidene carbonate are mainly organic lithium carbonates and lithium fluorides) can be covered on the surface of the negative electrode to reduce the consumption of the first additive and the second additive, prolong their repair effect on the SEI film (solid electrolyte interface film), thereby further improving the cycle performance of the energy storage device.

[0017] In a possible implementation, the cyclic sulfate includes one or more of propenyl-1,3-sultone and methylene disulfonate, and the cyclic carbonate includes at least one of fluorovinylidene carbonate and vinylene carbonate.

[0018] In one possible embodiment, the content of the auxiliary additive is 0.01wt% to 2wt% based on the mass of the electrolyte, which can ensure that the auxiliary additive does not excessively form a film at the interface between the electrolyte and the negative electrode plate, thereby ensuring the improvement of the room temperature cycle performance, high temperature cycle performance and high temperature storage performance of the lithium-ion battery.

[0019] An embodiment of the present application further provides an energy storage device, which includes a positive electrode plate, a negative electrode plate, and the electrolyte as described above, wherein the electrolyte infiltrates at least a portion of the positive electrode plate and at least a portion of the negative electrode plate. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0021] The embodiment of the present application provides an energy storage device, which includes a housing, a battery cell and an electrolyte. Specifically, the battery cell is installed on the inner side of the housing, and the electrolyte is injected into the inner side of the housing and soaks the battery cell. In the embodiment of the present application, the energy storage device is a secondary battery. Exemplarily, the secondary battery can be a lithium-ion battery.

[0022] The battery cell includes a positive electrode sheet, a separator, a negative electrode sheet, a positive electrode ear and a negative electrode ear. The separator is located between the positive electrode sheet and the negative electrode sheet, the positive electrode ear is electrically connected to the positive electrode sheet, and the negative electrode ear is electrically connected to the negative electrode sheet. Exemplarily, the positive electrode sheet, the separator, and the negative electrode sheet can be stacked in sequence, wound to form a bare battery cell, and then the positive electrode ear and the negative electrode ear are welded to prepare the battery cell.

[0023] Wherein, the positive electrode plate includes a positive electrode current collector and a positive electrode active layer covering the surface of the positive electrode current collector. Exemplarily, the positive electrode current collector is aluminum foil. The positive electrode material layer includes materials such as positive electrode active materials and additives. Exemplarily, the positive electrode active material is lithium iron phosphate. Wherein, the additives in the positive electrode material layer include conductive agents, binders and thickeners. Exemplarily, the conductive agent can be conductive carbon black SP (Super P). Exemplarily, the binder includes any one or more of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate (polyacrylate), polyvinylether (polyvinylether), polymethyl methacrylate (PMMA), polyhexafluoropropylene (Polyhexafluoropropylene) and styrene butadiene rubber (SBR). Exemplarily, based on the mass of the positive electrode material layer, the mass fraction of the binder is 2wt% to 4wt%, which is beneficial for bonding other components in the positive electrode material layer to prevent the positive electrode material layer from falling off. On the other hand, it can avoid the problem of excessive resistance of the positive electrode material layer due to excessive binder, thereby affecting the discharge capacity of the assembled energy storage device.

[0024] The diaphragm may adopt an existing battery diaphragm, and exemplarily, the diaphragm is a polyethylene (PE) film. The negative electrode plate includes a negative electrode current collector and a negative electrode active layer covering the surface of the negative electrode current collector. Exemplarily, the negative electrode current collector is copper foil, aluminum foil, etc. The negative electrode active layer includes materials such as negative electrode active materials and additives. Exemplarily, the negative electrode active material is artificial graphite. Among them, the additives in the negative electrode active layer include materials such as conductive agents, thickeners, and binders. Exemplarily, the conductive agent is conductive carbon black SP (Super P) and the thickener is carboxymethyl cellulose (Carboxymethyl Cellulose, CMC). Exemplarily, the binder includes any one or more of polyvinylidene fluoride (PVDF), polyamide (PA), polyacrylonitrile (PAN), polyacrylate, polyvinylether, polymethyl methacrylate (PMMA), polyhexafluoropropylene or styrene butadiene rubber (SBR). Exemplarily, based on the mass of the negative electrode material layer, the mass fraction of the binder is 2wt% to 4wt%, which is beneficial to bonding other components in the negative electrode material layer to avoid powdering of the negative electrode material layer, and on the other hand, it can avoid the problem of excessive resistance of the negative electrode material layer due to excessive binder, thereby affecting the discharge capacity of the assembled energy storage device.

[0025] The electrolyte infiltrates at least a portion of the negative electrode sheet and at least a portion of the positive electrode sheet to achieve electrolyte infiltration of the battery cell. In the present embodiment, the electrolyte is a non-aqueous electrolyte. Among them, the electrolyte includes an electrolyte salt, an organic solvent and an additive. In the present embodiment, the electrolyte salt is an alkali metal salt. Exemplarily, the alkali metal salt includes but is not limited to lithium salts and sodium salts. Exemplarily, the organic solvent includes at least one of a cyclic carbonate and a chain carbonate. Among them, exemplary, the cyclic carbonate includes one or more of ethylene carbonate and propylene carbonate. Exemplarily, the chain carbonate includes one or more of dimethyl carbonate, diethyl carbonate and methyl ethyl carbonate.

[0026] Exemplarily, based on the mass of the electrolyte, the mass fraction of the organic solvent is 60wt% to 85wt%, that is, the organic solvent accounts for. Specifically, the mass fraction of the organic solvent in the electrolyte is 60wt% to 85wt%. Specifically, the mass fraction of the organic solvent can be 60wt%, 65wt%, 70wt%, 75wt%, 80wt%, 85wt%, etc., and any value between the above values.

[0027] In the embodiment of the present application, the additive includes a first additive and a second additive. The first additive is a fluorophenylboric acid additive, and the fluorophenylboric acid additive has a structural formula as shown in formula (I):

[0028] Wherein, R1-R5 are each independently selected from one or more of fluorine, hydrogen, and fluoroalkyl, and R1-R5 are not hydrogen at the same time.

[0029] Among them, the solubility of the first additive decreases with the increase of the fluorination degree of the fluoroalkyl group. When the first additive is connected with a fluoroalkyl group greater than C3, the first additive is easily precipitated in the electrolyte, thereby affecting the storage performance of the electrolyte. Exemplarily, the fluoroalkyl group selected from R1 to R5 in the first additive is a fluoroalkyl group of C1 to C3. In some embodiments, R1 to R5 are each independently selected from one or more of fluorine, hydrogen, fluoromethyl, difluoromethyl and trifluoromethyl.

[0030] Exemplarily, in some embodiments, the first additive is selected from one or more of structural formula (I-1) to structural formula (I-3):

[0031]

[0032] Wherein, the second additive is a fluoropyridine additive, and the fluoropyridine additive has a structural formula as shown in formula (II):

[0033] Wherein, R6 to R10 are each independently selected from one or more of fluorine, hydrogen, and fluoroalkyl, and R6 to R10 are not hydrogen at the same time.

[0034] The solubility of the second additive decreases as the degree of fluorination of the fluoroalkyl group increases. When the second additive is connected with a fluoroalkyl group greater than C3, the second additive is easily precipitated in the electrolyte, thereby affecting the storage performance of the electrolyte. Exemplarily, the fluoroalkyl group selected from R6 to R10 in the second additive is a fluoroalkyl group of C1 to C3. In some embodiments, R6 to R10 are each independently selected from one or more of fluorine, hydrogen and trifluoromethyl.

[0035] Exemplarily, in some embodiments, the second additive is selected from one or more of structural formula (II-1) to structural formula (II-3):

[0036]

[0037] In the electrolyte provided above, the first additive and the second additive are used in combination, and there is an intermolecular interaction between the first additive and the second additive, which affects the reaction mechanism of each other, so that the first additive and the second additive undergo a reduction reaction at the same time. The following takes the first additive as structural formula (I-3) and the second additive as structural formula (II-1) as an example to specifically explain the mechanism of the combined use of the first additive and the second additive.

[0038] If the first additive is added to the electrolyte alone, the first additive of structural formula (I-3) undergoes the following reduction reaction process to form structure ①:

[0039]

[0040] If the second additive is added to the electrolyte alone, the second additive of structural formula (II-1) undergoes the following reduction reaction process to form structure ②:

[0041]

[0042] In the electrolyte of the embodiment of the present application, the first additive and the second additive are used together, and the interaction process between the first additive and the second additive is as follows:

[0043]

[0044] Among them, the B (boron) atom in the structure of the first additive is electron-deficient, and the N (nitrogen) atom in the structure of the second additive is electron-rich. The first additive and the second additive have intermolecular interactions, which can affect each other's reaction mechanism, so that the first additive and the second additive can simultaneously undergo the following reduction reaction process to form structure ③:

[0045]

[0046] Specifically, the fluorophenyl radicals produced by the reaction of the first additive have strong electrophilicity, making it easier to attack the second additive. The first additive will transfer charge to the second additive during the reduction process, reducing the LUMO (Lowest Unoccupied Molecular Orbital) energy level of the molecular cluster, thereby causing the first additive and the second additive to undergo a reduction reaction at the same time. At the same time, compared with the structure ① formed by adding the first additive alone or the structure ② formed by adding the second additive alone to the electrolyte, the pyridine-based N atom contains a lone pair of electrons, which has a stronger binding effect on lithium ions, making structure ③ more difficult to be reduced, and the phenyl group in structure ③ has a large conjugated system, making structure ③ more difficult to be oxidized, so that structure ③ is more stable relative to structure ① and structure ②, thereby making the negative electrode stability of the decomposition product formed by the combined action of the first additive and the second additive higher, so that the negative electrode interface can be stabilized during the cycle of the assembled energy storage device, while reducing the loss of active lithium, which is beneficial to improving the capacity retention rate of the energy storage device under high temperature conditions, and thus is beneficial to improving the performance of the energy storage device under high temperature conditions.

[0047] Wherein, based on the mass of the electrolyte, the mass fraction of the first additive is a, and the mass fraction of the second additive is b. Exemplarily, the mass fraction a of the first additive is 0.01wt% to 5wt%, that is, the mass proportion of the first additive in the electrolyte is 0.01wt% to 5wt%. Specifically, the mass fraction a of the first additive can be 0.01wt%, 0.1wt%, 0.2wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, and any values ​​between the above values. Exemplarily, the mass fraction b of the second additive is 0.01wt% to 5wt%, that is, the mass proportion of the second additive in the electrolyte is 0.01wt% to 5wt%. Specifically, the mass fraction b of the first additive can be 0.01wt%, 0.1wt%, 0.2wt%, 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, and any values ​​between the above values.

[0048] Exemplarily, 0.02wt%≤a+b≤10wt%, that is, the total mass of the first additive and the second additive in the electrolyte accounts for 0.02wt% to 10wt%. Specifically, a+b can be 0.02wt%, 0.5wt%, 1wt%, 2wt%, 4wt%, 6wt%, 8wt%, 10wt%, and any value in between.

[0049] Exemplarily, 0.1≤a / b≤5. Specifically, a / b can be 0.1, 0.2, 0.5, 1, 2, 3, 4, 5, etc., and any value between the above values.

[0050] In an embodiment of the present application, the additives in the electrolyte also include auxiliary additives, which can be used to further improve the high-temperature storage performance of the energy storage device formed by assembling the electrolyte. In this embodiment, the auxiliary additives include one or more of cyclic sulfates and cyclic carbonates. Among them, exemplarily, the cyclic sulfates include but are not limited to one or more of propylene-1,3-sultone and methylene methanedisulfonate (MMDS). Exemplarily, the cyclic carbonates include one or more of fluoroethylene carbonate and vinylene carbonate. The mechanism of action of auxiliary additives such as cyclic sulfates or cyclic carbonates is as follows: the molecules of this type of auxiliary additives have a strong binding effect with lithium ions and can be reduced at the negative electrode interface during formation. The reduction products (such as the reduction products of cyclic sulfates are mainly organic lithium sulfates and lithium sulfonates, and the reduction products of cyclic carbonates such as fluorovinylidene carbonate are mainly organic lithium carbonates and lithium fluorides) can cover the surface of the negative electrode to reduce the consumption of the first additive and the second additive, prolong their repair effect on the SEI film (solid electrolyte interface film), thereby further improving the cycle performance of the energy storage device.

[0051] Exemplarily, based on the mass of the electrolyte, the mass fraction c of the auxiliary additive is 0.01wt% to 2wt%, that is, the mass fraction of the auxiliary additive in the electrolyte is 0.01wt% to 2wt%. Specifically, the mass fraction c of the auxiliary additive can be 0.01wt%, 0.1wt%, 0.2wt%, 0.5wt%, 1wt%, 2wt%, and any value between the above values.

[0052] The following is an explanation in conjunction with specific experiments. Among them, the experimental groups P1-P15 and groups N1-N5 both provide an energy storage device, and the energy storage device is exemplified by a lithium-ion battery, which is specifically prepared according to the following steps:

[0053] Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate, conductive carbon black SP, and binder PVDF are dispersed in the solvent NMP (N-Methylpyrrolidone) according to the mass ratio of 97:0.7:2.3, and mixed evenly to obtain positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and after drying, cold pressing, slitting, and cutting, the positive electrode sheet is obtained. Among them, the positive electrode slurry coating forms the positive electrode active layer.

[0054] Preparation of negative electrode sheet: artificial graphite, conductive carbon SP, thickener CMC and binder SBR are dispersed in deionized water according to the mass ratio of 96.5:0.5:1:2 and mixed evenly to obtain negative electrode slurry, which is then coated on the negative electrode current collector aluminum foil, and then dried, cold pressed, slit and cut to obtain negative electrode sheet. The negative electrode slurry coating forms the negative electrode active layer.

[0055] Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) are mixed in a mass ratio of 2:1:2, and then the electrolyte salt lithium hexafluorophosphate is dissolved in the solvent, stirred until completely dissolved and uniformly dissolved, and the additives are added and mixed to obtain the electrolyte. Among them, the types and amounts of additives in the electrolytes of groups P1-P15 and groups N1-N5 are shown in Table 1.

[0056] Preparation of diaphragm: 16um polyethylene film is used as diaphragm.

[0057] Preparation of lithium-ion batteries: stack the prepared positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is in the middle of the positive electrode sheet and the positive and negative electrode sheets to separate the positive electrode sheet from the positive and negative electrode sheets, and then wind them to obtain a bare cell, and then weld the positive and negative ears to obtain a cell. Assemble the cell into the shell, inject the prepared electrolyte, and then package, stand, form, shape, and perform capacity testing on the cell to finally prepare a lithium-ion battery.

[0058] Lithium-ion batteries of groups P1-P15 and N1-N5 were taken to measure the 25°C cycle performance, 45°C cycle performance and 60°C cell volume expansion rate of the lithium-ion batteries, and the results are shown in Table 2. The test process of the 25°C cycle performance of the lithium-ion battery is as follows: the lithium-ion battery is subjected to a charge and discharge cycle test on a charge and discharge instrument, the test temperature is 25°C, the cycle rate is 1C (i.e., the charge rate and the discharge rate are both 1C), the charging voltage is 2.5V to 3.65V, and the capacity retention rate after the cycle is calculated. The capacity retention rate calculation formula for the 25°C cycle is: capacity retention rate after the nth cycle = (discharge capacity after the nth cycle / discharge capacity of the first cycle) * 100wt%.

[0059] The test process of the 45℃ cycle performance of lithium-ion batteries is as follows: the lithium-ion battery is subjected to a charge and discharge cycle test on a charge and discharge instrument, the test temperature is 45℃, the cycle rate is 1C (i.e., both the charge rate and the discharge rate are 1C), the charging voltage is 2.5V to 3.65V, and the capacity retention rate after the cycle is calculated. The capacity retention rate calculation formula for the 45℃ cycle is: capacity retention rate after the nth cycle = (discharge capacity after the nth cycle / discharge capacity of the first cycle) * 100wt%.

[0060] The test process of the volume expansion rate of the lithium-ion battery cell at 60°C is as follows: adjust the temperature of the constant temperature box to 25°C, let it stand for 10 minutes, charge at a constant current of 0.5C to 3.65V, then charge at a constant voltage of 3.65V to 0.05C cutoff, let it stand for 30 minutes, and test the initial fully charged volume V0 of the cell; adjust the temperature of the constant temperature box to 60°C, let it stand for 30 minutes, charge at a constant current of 0.5C to 3.65V, let it stand for 1 hour, cycle twice for replenishing power, store for 60 days, cool the cell, and test the fully charged volume V1 of the cell at this time; then the volume expansion rate of the cell stored at 60°C for 60 days = (V1 / V0-1)×100wt%.

[0061] Table 1 Composition and ratio of the electrolyte components in lithium-ion batteries of groups P1-P15 and N1-N5

[0062]

[0063]

[0064] Table 2 Performance of lithium-ion batteries in groups P1-P15 and N1-N5

[0065]

[0066]

[0067] It can be seen from Tables 1 and 2 that the first additive of fluorophenylboric acid and the second additive of fluoropyridine were not added to the electrolyte of group N1, and the capacity retention rate of the obtained lithium-ion battery after 500 cycles at 25°C and 45°C was low, and the volume expansion rate was high when stored at 60°C for 60 days. The lithium-ion battery has poor room temperature cycle performance, high temperature cycle performance and high temperature storage performance.

[0068] By comparing group N1 and group P4-P6, the electrolyte of group P4-P6 is added with a second additive of fluoropyridine alone, which can effectively improve the cycle performance of lithium-ion batteries at room temperature. At the same time, due to the high film-forming reactivity of fluorine atoms in fluoropyridine compounds, the cycle of lithium-ion batteries at 45°C can be effectively stabilized, thereby improving the high-temperature cycle performance of lithium-ion batteries. By comparing group P1-P3 and group P4-P6, the electrolyte of group P1-P3 is added with a first additive of fluorophenylboric acid alone. When fluorophenylboric acid compounds are used as additives, the lithium metaborate in their reduction products has higher high-temperature stability. Therefore, the first additives of structural formula (I-1) to structural formula (I-3) have a significantly better high-temperature improvement effect on the battery cell than the second additives of structural formula (II-1) to structural formula (II-3).

[0069] By comparing groups P7-P15 and group N1, the first additive of fluorophenylboronic acid and the second additive of fluoropyridine were added to the electrolyte of groups P7-P15 at the same time, and the cycle performance of the assembled lithium-ion battery at 25°C and 45°C was improved, and the volume expansion rate after storage at 60°C for 60 days was also reduced. The experimental results show that by adding the first additive of fluorophenylboronic acid and the second additive of fluoropyridine to the electrolyte, the normal temperature cycle performance, high temperature cycle performance and high temperature storage performance of the assembled energy storage device can be improved.

[0070] Among them, by comparing the lithium-ion batteries of groups P7-P9 with groups P1-P3 and groups P4-P6, compared with the lithium-ion batteries of groups P1-P3 to which the first additive was added alone, and the lithium-ion batteries of groups P4-P6 to which the second additive was added alone, the cycle performance of the lithium-ion batteries of groups P7-P9 at room temperature 25°C and high temperature 45°C were improved, and the volume expansion rate stored at high temperature 60°C for 60 days was reduced. The experimental results show that when the first additive and the second additive are used in combination, the protection effect on the room temperature and high temperature of the battery cell is better than adding the first additive alone or adding the second additive alone. This is because when the first additive of fluorophenylboronic acid and the second additive of fluoropyridine are used in combination, the second additive of fluoropyridine can transfer the molecular charge to the first additive of fluorophenylboronic acid during the reduction process, thereby reducing the electronic energy of the overall cluster, promoting the degradation of the first additive and the second additive, and ultimately resulting in the formation of the SEI interface layer (solid electrolyte interface layer) with more components mainly composed of benzopyridine lithium compounds. The pyridine group in benzopyridine lithium compound has weaker aromaticity and contributes less to the conjugated electron cloud, which makes the electronic insulation of the SEI interface layer higher, thereby ensuring the stable high-temperature performance of the lithium-ion battery, and further improving the high-temperature cycling performance and high-temperature storage performance of the energy storage device.

[0071] By comparing group P7 and group P10-P12, as the total amount of the first additive and the second additive added increases, the first additive and the second additive's effect on the normal temperature cycle and high temperature cycle of the lithium-ion battery first gradually increases, and then gradually decreases as the total amount added increases. This is because as the total amount of the first additive and the second additive added increases, the first additive and the second additive will consume a large amount of active lithium when forming the SEI film (solid electrolyte interface film). Excessive addition of the first additive and the second additive will affect the overall active lithium content of the lithium-ion battery, which will lead to a decrease in the discharge capacity of the lithium-ion battery, and further cause the normal temperature cycle performance and high temperature cycle performance of the lithium-ion battery to decrease. In addition, when too much of the first additive and the second additive are added, the film formation of the excess additive on the negative electrode surface during the cycle will cause an increase in the thickness of the negative electrode and the gas production during the cycle, resulting in an increase in the volume expansion rate of the lithium-ion battery when stored at a high temperature of 60°C for 60 days, thereby reducing the high temperature storage performance of the lithium-ion battery.

[0072] In addition, by comparing group N4 and group P10-P12, 0.005wt% of the first additive and 0.005wt% of the second additive were added to the electrolyte of group N4, wherein the amount of the first additive and the second additive added was small, and the negative electrode film formation was incomplete, so the improvement effect on the high temperature storage performance of the lithium-ion battery was not obvious. After a large number of experimental studies, the embodiments of the present application found that when the mass fraction a of the first additive and the mass fraction b of the second additive in the electrolyte meet the following conditions: 0.02wt%≤a+b≤10wt%, it can ensure that the assembled energy storage device has good room temperature cycle performance, high temperature cycle performance and high temperature storage performance.

[0073] In addition, when the first additive and the second additive are used in combination, there is an intermolecular interaction between the first additive and the second additive, which will affect each other's reaction mechanism. After a large number of experimental studies, the embodiments of the present application found that when the mass fraction a of the first additive and the mass fraction b of the second additive in the electrolyte satisfy: 0.1≤a / b≤5, it can ensure that the assembled energy storage device has good room temperature cycle performance, high temperature cycle performance and high temperature storage performance.

[0074] By comparing groups P1-P6 and groups N2-N4, 10wt% of the first additive is added to the electrolyte of group N2, and 10wt% of the second additive is added to the electrolyte of group N3. Although there is a sufficient amount of film-forming additives in the lithium-ion batteries of groups N2 and N3 to participate in the negative electrode film formation, the consumption of active lithium by the polyfluorinated additives during the film formation process will generally improve the cycle performance of the lithium-ion battery. The embodiments of the present application have been found through a large number of experimental studies that the mass fraction a of the first additive in the electrolyte is controlled at 0.01wt%≤a≤5wt%, and the mass fraction b of the second additive is controlled at 0.01wt%≤b≤5wt%, which can enable the assembled lithium-ion battery to have good room temperature cycle performance, high temperature cycle performance and stable high temperature storage performance.

[0075] In addition, by comparing Group P7 with Group P15, in addition to the first additive and the second additive, the electrolyte of Group P15 also adds cyclic sulfate methylene disulfonate (MMDS) as an auxiliary additive, so that the room temperature cycle performance, high temperature cycle performance and high temperature storage performance of the lithium-ion battery of Group P15 are further improved. This is because the cyclic sulfate methylene disulfonate has a strong binding effect with lithium ions, and can be reduced at the interface between the electrolyte and the negative electrode plate in the early stage of SEI film formation to form an interface layer containing lithium sulfonate (mainly organic lithium sulfate and lithium sulfonate). The interface layer has good electrochemical stability, reduces the consumption of the first additive and the second additive during the formation period, thereby reducing the room temperature cycle performance and high temperature cycle performance of the lithium-ion battery, and can improve the high temperature storage performance of the lithium-ion battery. In addition, through research, the present application also found that, similar to the reaction mechanism of cyclic sulfates, cyclic carbonates such as fluoroethylene carbonate or vinylene carbonate also have a strong binding effect with lithium ions, and can be reduced at the interface between the electrolyte and the negative electrode plate to generate an organic interface layer (the main components are organic lithium carbonate and lithium fluoride). This interface layer can cover the surface of the negative electrode plate to reduce the consumption of the first additive and the second additive, prolonging the repair effect on the SEI film, thereby reducing the room temperature cycle performance and high temperature cycle performance of the lithium-ion battery, and can improve the high temperature storage performance of the lithium-ion battery.

[0076] By comparing group N5 and group P15, the experimental results show that when the amount of cyclic sulfate added is too much, it is easy to cause the cycle performance and high temperature storage performance of the lithium-ion battery to decrease. This is because when the cyclic sulfate is added in excess, it is easy to form excessive film at the interface between the electrolyte and the negative electrode during the formation and circulation process, which is easy to cause the continuous increase in the loss of active lithium during the cycle of the lithium-ion battery, thereby increasing the risk of deterioration of the cycle performance of the lithium-ion battery. At the same time, the accumulation of the reaction products of the cyclic sulfate and the enrichment of the gas production are also easy to cause the increase of the impedance of the battery cell in the lithium-ion battery and the risk of disconnection of the positive and negative electrodes, so it is necessary to control the amount of auxiliary additives added. The embodiment of the present application has been found through a large number of experimental studies that the mass fraction c of the auxiliary additive in the electrolyte satisfies 0.01wt%≤c≤2wt%, which can ensure that the auxiliary additive will not form excessive film at the interface between the electrolyte and the negative electrode, thereby ensuring the improvement effect of the normal temperature cycle performance, high temperature cycle performance and high temperature storage performance of the lithium-ion battery.

[0077] In addition, by comparing group N5 and group P3-P4, the mass fraction c of the auxiliary additive in the electrolyte of group N5 and group P3-P4 does not satisfy 0.01wt%≤c≤2wt%, and the first additive and the second additive are added to the electrolyte of group N5 at the same time, the first additive is added to the electrolyte of group P3, and the second additive is added to the electrolyte of group P4. The experimental results show that the lithium-ion battery formed by the electrolyte assembly of group N5 has better room temperature cycle performance, high temperature cycle performance and stable high temperature storage performance. The experimental results once again assist in proving that the first additive and the second additive provided in the embodiment of the present application have a synergistic effect, and the combined use of the first additive and the second additive can improve the room temperature cycle performance, high temperature cycle performance and high temperature storage performance of the lithium-ion battery formed by the electrolyte assembly.

[0078] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiments and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. An electrolyte, characterized in that: The electrolyte includes a first additive and a second additive, wherein the first additive has a structural formula as shown in formula (I): wherein R1 to R5 are each independently selected from one or more of fluorine, hydrogen, and fluoroalkyl, and R1 to R5 are not hydrogen at the same time; The second additive has a structural formula as shown in formula (II): Wherein, R6 to R10 are each independently selected from one or more of fluorine, hydrogen, and fluoroalkyl, and R6 to R10 are not hydrogen at the same time.

2. The electrolyte according to claim 1, characterized in that The fluoroalkyl groups selected from R1 to R5 are C1 to C3 fluoroalkyl groups, and the fluoroalkyl groups selected from R6 to R10 are C1 to C3 fluoroalkyl groups.

3. The electrolyte according to claim 1, characterized in that R1-R5 are each independently selected from one or more of fluorine, hydrogen, fluoromethyl, difluoromethyl and trifluoromethyl, and R6-R10 are each independently selected from one or more of fluorine, hydrogen and trifluoromethyl.

4. The electrolyte according to any one of claims 1 to 3, characterized in that The first additive is selected from one or more of structural formula (I-1) to structural formula (I-3):

5. The electrolyte according to any one of claims 1 to 3, characterized in that The second additive is selected from one or more of structural formula (II-1) to structural formula (II-3):

6. The electrolyte according to any one of claims 1 to 3, characterized in that Based on the mass of the electrolyte, the mass fraction of the first additive is a, the mass fraction of the second additive is b, and 0.02wt%≤a+b≤10wt%.

7. The electrolyte according to claim 6, characterized in that 0.1≤a / b≤5.

8. The electrolyte according to any one of claims 1 to 3, characterized in that: The electrolyte further includes an auxiliary additive, and the auxiliary additive is one or more of cyclic sulfate and cyclic carbonate.

9. The electrolyte according to claim 8, characterized in that The cyclic sulfate includes one or more of propenyl-1,3-sultone and methylene disulfonate, and the cyclic carbonate includes at least one of fluorovinylidene carbonate and vinylene carbonate.

10. The electrolyte according to claim 8, characterized in that Based on the mass of the electrolyte, the content of the auxiliary additive is 0.01wt% to 2wt%.

11. An energy storage device, characterized in that: The energy storage device comprises a positive electrode sheet, a negative electrode sheet and an electrolyte as claimed in any one of claims 1 to 10, wherein the electrolyte soaks at least a portion of the positive electrode sheet and at least a portion of the negative electrode sheet.